Stability of goal orientations in Dutch talented adoslecent field hockey players - Elferink-Gemser, M. T.; Starkes, J.; Medic, N.; Visscher, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction: The adolescent period is characterized by extreme changes in virtually every aspect of an athlete`s performance. To ultimately meet international performance standards later on, athletes have to develop their physical, physiological, and technical performance characteristics fairly quickly (Elferink-Gemser et al., 2006; 2007). However, is this also the case for psychological variables such as motivation? With the importance of goal orientations in understanding achievement motivation in sport and exercise being widely recognized by researchers (e.g., Duda, 1992), the purpose of this study was to examine how stable task and ego orientation are for talented adolescent athletes. Methods Participants were 41 (20 male and 21 female; mean age 14.0, sd 1.1 at the first measurement) talented field hockey players who filled in the Task and Ego Orientation in Sport Questionnaire (TEOSQ; Duda and Nicholls, 1992) four times over a 4-year period. Results: Intra-class coefficients, the percentage of participants with differences that were within ±1 range of the mean test scores (proportion of agreement test), repeated measures MANOVA, and paired sample t-test scores showed that players` goal orientations changed marginally from year-to-year and across a period of 4 years (p>.05). Discussion: In order to persevere in a highly competitive environment, talented athletes require high levels of both task and ego orientation (Van Yperen and Duda, 1999). The results in the present study confirm relatively high scores on task as well as ego orientation for both male and female talented field hockey players, with task orientation scores comparable to other studies and ego orientation scores higher (Duda and Whitehead, 1998). The results also show that motivational orientations appear to be highly stable over a 4-year period and independent of one`s relative skill or physical maturity. An implication of these findings is that one measure of an athlete`s goal orientations during adolescence appears to be sufficient. Whether these results are specific for Dutch field hockey players or whether they can be generalized to other populations of adolescent talented athletes has to be investigated. The results are unique because this is one of the first studies to apply a longitudinal design examining the stability of talented adolescent athletes` goal orientations over a period of four years.